1994
DOI: 10.1007/bf00244027
|View full text |Cite
|
Sign up to set email alerts
|

Specific tension of elbow flexor and extensor muscles based on magnetic resonance imaging

Abstract: Series cross-section images of the upper extremity were obtained for four men by magnetic resonance imaging (MRI) and anatomical cross-sectional areas (ACSA) of elbow flexor muscles [biceps brachii (BIC), brachialis (BRA), brachioradialis (BRD)] and extensor muscles [triceps brachii (TRI)] were measured. Physiological cross-sectional area (PCSA) was calculated from the muscle volume and muscle fibre length, the former from the series ACSA and the latter from the muscle length multiplied by previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 28 publications
6
86
1
6
Order By: Relevance
“…2) might to a part be due to the mechanical output of the remaining muscles crossing the elbow (Buchanan et al, 1989). However, when force estimates of the BB improve, this should yield a closer correspondence with the total elbow flexion force as well, given the large contribution of BB to elbow flexion force (Kawakami et al, 1994). It should be noted that in all tests we compare the same data with only the BB EMG data processed differently, this means that when the activation of synergists or antagonists fluctuates during the trial, this lowers the correlation between EMG and force, but it does not bias our comparisons.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2) might to a part be due to the mechanical output of the remaining muscles crossing the elbow (Buchanan et al, 1989). However, when force estimates of the BB improve, this should yield a closer correspondence with the total elbow flexion force as well, given the large contribution of BB to elbow flexion force (Kawakami et al, 1994). It should be noted that in all tests we compare the same data with only the BB EMG data processed differently, this means that when the activation of synergists or antagonists fluctuates during the trial, this lowers the correlation between EMG and force, but it does not bias our comparisons.…”
Section: Limitationsmentioning
confidence: 99%
“…Different electrode configurations were tested (proximal-distal of the innervation zone, medio-lateral and longitudinal to muscle fibers) and the resulting muscle activation estimate was related to normalized elbow flexion force. Although the normalized flexion force is obviously determined by multiple synergistic and antagonistic muscles, BB is expected to be a major contributor (Kawakami et al, 1994). Hence we reasoned that any reduction in the difference between the EMG amplitude and the flexion force would reflect a better estimate of the contribution of the BB to the elbow moment, and thus a better estimate of activation of especially the BB.…”
Section: Introductionmentioning
confidence: 99%
“…Kawakami et al, 1994). So far, its activity was mainly measured with intramuscular EMG (e.g., Buchanan et al, 1986;Rudroff et al, 2008;van Bolhuis et al, 1997;van Zuylen et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The elbow flexor muscles are the brachialis (BR), biceps brachii (BB) and brachioradialis (BRR, Murray et al, 2000), with the greatest contribution to elbow flexion from the BR as shown with magnetic resonance imaging (Kawakami et al, 1994). So far, activity of this important elbow flexor has mainly be measured with intramuscular electromyography (EMG, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…F f é a força dos flexores primários do braço; 63 é a tensão específica dos flexores (Newton/cm 2 ) (18) ; e A f representa a área dos músculos flexores do braço. Em seguida, o último passo foi estimar a capacidade máxima de geração de força dos músculos flexores primários do braço.…”
Section: Figura 4 Posição Adotada Pelo Sujeito Para Realização Dos Tunclassified